2019
DOI: 10.1038/s41586-019-1643-z
|View full text |Cite|
|
Sign up to set email alerts
|

Subducting carbon

Abstract: A hidden carbon cycle exists inside Earth. Every year, megatons of carbon disappear into subduction zones, affecting atmospheric carbon dioxide and oxygen over Earth's history. Here we discuss the processes that move carbon towards subduction zones and transform it into fluids, magmas, volcanic gases and diamonds. The carbon dioxide emitted from arc volcanoes is largely recycled from subducted microfossils, organic remains and carbonate precipitates. The type of carbon input and the efficiency with which carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
268
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 358 publications
(278 citation statements)
references
References 108 publications
(137 reference statements)
7
268
1
2
Order By: Relevance
“…It has long been recognized that subducted carbonate and organic carbon contributes to the CO 2 degassing from volcanoes (Allard, ; Marty & Jambon, ; Sano & Marty, ; Sano & Williams, ), that sufficient carbon is subducted under a specific volcano to supply its measured CO 2 flux (Fischer et al, ), and that along entire arcs more carbon is subducted than what is emitted through the volcanoes (Hilton et al, ). The most recent evaluation of subducted carbon inputs and volcanic CO 2 output supports earlier ideas that more subducted organic‐ and carbonate‐derived C is supplied to the zone of arc magma generation than what is released back to the atmosphere through volcanism (Plank & Manning, ). The idea that limestone‐sourced crustal carbon contributes to the high CO 2 flux measured at a volcano was probably first quantitatively introduced by Goff et al (), who showed that during heightened activity at Popocatepetl in 1997, C/S ratios increased intermittently from the usual background levels of <8 to up to 140 measured by Fourier Transform Infrared (FTIR) in the plume.…”
Section: Challenges and Open Questions For Future Researchsupporting
confidence: 61%
See 1 more Smart Citation
“…It has long been recognized that subducted carbonate and organic carbon contributes to the CO 2 degassing from volcanoes (Allard, ; Marty & Jambon, ; Sano & Marty, ; Sano & Williams, ), that sufficient carbon is subducted under a specific volcano to supply its measured CO 2 flux (Fischer et al, ), and that along entire arcs more carbon is subducted than what is emitted through the volcanoes (Hilton et al, ). The most recent evaluation of subducted carbon inputs and volcanic CO 2 output supports earlier ideas that more subducted organic‐ and carbonate‐derived C is supplied to the zone of arc magma generation than what is released back to the atmosphere through volcanism (Plank & Manning, ). The idea that limestone‐sourced crustal carbon contributes to the high CO 2 flux measured at a volcano was probably first quantitatively introduced by Goff et al (), who showed that during heightened activity at Popocatepetl in 1997, C/S ratios increased intermittently from the usual background levels of <8 to up to 140 measured by Fourier Transform Infrared (FTIR) in the plume.…”
Section: Challenges and Open Questions For Future Researchsupporting
confidence: 61%
“…Summary of global volcanic and tectonic CO 2 degassing in teragrams of CO 2 per year as discussed in the text. The subduction input flux is from Plank and Manning (), and the mid‐ocean ridge degassing flux is from Le Voyer et al ().…”
Section: Challenges and Open Questions For Future Researchmentioning
confidence: 99%
“…Organic matter can be an important constituent of oceanic sediments (Mayer et al, 1992), and on average it accounts for less than 1 wt.% (Kelemen and Manning, 2015). Nevertheless, organic matter in deep-sea fans can dominate the carbon input flux at some margins (Plank and Manning, 2019). The proportion of organic to inorganic carbon (i.e., marine carbonates) subducted globally is about 20% (Plank and Manning, 2019) and the total amount of organic carbon subducted in modern active subduction zones is estimated >11 Mt C/y (Clift, 2017).…”
Section: Implications For Organic Matter Dissolution At Subduction Zonesmentioning
confidence: 99%
“…The dissolution of graphitic carbon in aqueous fluids due to oxidation or reduction processes (Connolly and Cesare, 1993;Connolly, 1995;Zhang et al, 2018;Tumiati and Malaspina, 2019b) is of primary importance as it governs the removal of organic matter from the sediments flushed by fluids released from the dehydrating subducted plate (Schmidt and Poli, 2013). In contrast to carbonates (e.g., Kelemen and Manning, 2015), graphite has long been considered to represent a refractory sink of carbon in the subducting slab (Plank and Manning, 2019), showing low solubility in metamorphic fluids (Connolly and Cesare, 1993) and silicate melts (Duncan and Dasgupta, 2017). However, recent thermodynamic models and experiments suggest that graphite can be readily dissolved in subduction fluids (Manning et al, 2013), stressing for instance the importance of pH and of dissolved silica (Tumiati et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CO 2 released via decarbonation and dissolution may be reincorporated into the slab by carbonation reactions driven by migrating fluids (e.g., Piccoli et al, 2016;Scambelluri et al, 2016). Finally, the amount of CO 2 and organic carbon delivered to subduction zones varies considerably in both space and time (Plank & Manning, 2019). The storage of CO 2 in the lithosphere is a major uncertainty in both models.…”
Section: Carbon Sources 311 Modern Degassing Estimatesmentioning
confidence: 99%